2013
DOI: 10.1183/09031936.00055513
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship between physical activity and lung health in patients with cystic fibrosis

Abstract: Exercise is beneficial for patients with cystic fibrosis (CF) but long-term effects of physical activity on lung function evolution are unknown. We evaluated the longitudinal relationship between changes in habitual physical activity (HPA) and rate of decline in lung function in patients with CF.We tracked HPA using the Habitual Activity Estimation Scale, forced expiratory volume in 1 s (FEV1) and Stage I exercise tests in 212 patients with CF over a 9-year period.Adjusting for sex, baseline age and FEV1, muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 36 publications
3
130
1
5
Order By: Relevance
“…Cox et al [4] reported higher scores in QoL by adult subjects with CF who performed ≥ 30 minutes of moderate-vigorous PA daily compared to those who performed <30 minutes daily. In a cross-sectional study on children with CF, PA was found to correlate quite strongly with QOL [7]. In our study we found a 9-points higher body image perception in the more active group, even if no statistical significance were detected in difference of QOL scores between groups previous studies reported similar results [29].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Cox et al [4] reported higher scores in QoL by adult subjects with CF who performed ≥ 30 minutes of moderate-vigorous PA daily compared to those who performed <30 minutes daily. In a cross-sectional study on children with CF, PA was found to correlate quite strongly with QOL [7]. In our study we found a 9-points higher body image perception in the more active group, even if no statistical significance were detected in difference of QOL scores between groups previous studies reported similar results [29].…”
Section: Discussionsupporting
confidence: 78%
“…Others described no significant differences in PA to healthy peers [2,7,10]. Regarding pulmonary function, some authors reported that higher PA levels were associated with a slower rate of decline in FEV 1 , specifically in girls with CF [5,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise in CF is increasingly recognised to be important to the maintenance of good lung function and bone health, and to the patient's sense of wellbeing [66,67]. The following three presentations at the ERS congress discussed physical activity levels and the potential benefits induced by an active lifestyle.…”
Section: Exercise and Physiotherapymentioning
confidence: 99%